Ethyl Vinyl Acetate (EVA) nanocomposites for biomedical applications: morphology and in vitro biostability - Abdulkader Mohamed Alakrach (School of Material Engineering, Universiti Malaysia Perlis, 2014)
The viability of Ethly Vinyl Acetate (EVA) filled nanoclay nanocomposites as candidate materials of biomedical devices was investigated, the in vitro biostability of the neat EVA and EVA nanocomposites was compared and accessed by exposing the materials in the oxidizing and hydrolytic agents, at temperature of 37 p0sC , the morphology of the neat EVA and EVA nanocomposites nanoclay filled was studied by using x-ray diffraction (XRD), Transmission Electron Microscopy (TEM) and scanning Electron Microscopy (SEM), while the physical properties upon the in vitro exposure were examined using tesile test, thermogravimetric analysis (TGA) and water permeability test.